2012
DOI: 10.3233/bmr-2012-0323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stretching program in an industrial workplace on hamstring flexibility and sagittal spinal posture of adult women workers: A randomized controlled trial

Abstract: Hamstring stretching exercises performed in the working place are effective for increasing hamstring muscle extensibility. This increase generates a more aligned thoracic curve and more anterior pelvic inclination when maximal trunk flexion is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 6 publications
3
72
0
8
Order By: Relevance
“…Regarding chronic effect of MSE in body posture, significant changes were observed in the spine in the concavities of the cervical and thoracic regions, asymmetries in the cervical region and on lumbar region curvature, as in accordance with outcomes in other studies (25,26) , but not in accordance with the study by Li et al (27) . Hashimoto et al (25) studied 11 individuals in average age of 37.1 years, during 3 to 4 months, and 20 sessions applied of one hour each, active stretching, 2 times per week; at the end of the study, the volunteers presented significant improvements in the leveling of the shoulders, hip, trunk and head.…”
Section: Sc Asymmetriessupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding chronic effect of MSE in body posture, significant changes were observed in the spine in the concavities of the cervical and thoracic regions, asymmetries in the cervical region and on lumbar region curvature, as in accordance with outcomes in other studies (25,26) , but not in accordance with the study by Li et al (27) . Hashimoto et al (25) studied 11 individuals in average age of 37.1 years, during 3 to 4 months, and 20 sessions applied of one hour each, active stretching, 2 times per week; at the end of the study, the volunteers presented significant improvements in the leveling of the shoulders, hip, trunk and head.…”
Section: Sc Asymmetriessupporting
confidence: 88%
“…Hashimoto et al (25) studied 11 individuals in average age of 37.1 years, during 3 to 4 months, and 20 sessions applied of one hour each, active stretching, 2 times per week; at the end of the study, the volunteers presented significant improvements in the leveling of the shoulders, hip, trunk and head. Finally, Muyor et al (26) evaluated 58 women, mean age 44.2 years, in which were subjected to 12 weeks of stretching of posterior thigh muscles, 3 times a week and, at the end of the study, they showed a more aligned thoracic curve.…”
Section: Sc Asymmetriesmentioning
confidence: 99%
“…Connective tissue compliance is considered a major factor in musculoskeletal flexibility [16]. Muyor et al [17] reported that the forward pelvic tilt angle increased after hamstring muscle stretching, and Feland et al [16] confirmed that pelvic mobility in the sagittal plane increased in elderly people after hamstring muscle stretching. The increase in the tension in the hamstring muscles when sitting with the soles of the feet in contact with the floor may restrict the pelvic forward tilt.…”
Section: Introductionmentioning
confidence: 52%
“…One factor that should influence the range of motion of the hip is the extensibility of the hamstrings, which drive the hip and knee as biarticular muscles. Hamstring stretching was shown to improve the pelvic anteversion angle [17] and the mobility of the hip in elderly individuals [16]. The sitting position in this study fixed the knee flexion angle at 90 , which should have increased hamstring tension during the measurement.…”
Section: The Relationship Between the Ability To Perform The Sit-to-smentioning
confidence: 99%
“…Stretching is often used with the aim of promoting accruals in range of motion (ROM) in different population types (1,2,3,4,5,6,7), favoring the improvement of the daily life functions and injuries recovering (8,9), despite controversies with respect to physical performance and pain relief after its application (10,11,12,13,14,15). The increasing in ROM is possible because the stretching techniques influence muscle extensibility and joint flexibility (16,17).…”
Section: Introductionmentioning
confidence: 99%